Hydroxypropyl-β-cyclodextrin-incorporated Pebax composite membrane for improved permselectivity in organic solvent nanofiltration. Issue 26 (7th June 2022) - Jia, Mengmeng; Liang, Yucang; Liu, Ziyang; Liu, Yue; Zhang, Xuehong; Guo, Hongxia
Abstract : The OSN membrane was prepared via crosslinking HP-β-CD in Pebax layer with TDI. The as-prepared membrane exhibited high methanol permeability and good dye rejections, as well as longer running stability. Abstract : Thanks to the characteristic hollow cavity structure and sustainable and nontoxic macrocycle molecule feature, cyclodextrins have been used as building block to fabricate organic solvent nanofiltration (OSN) membranes with enhanced permeability and selectivity. Herein, hydroxypropyl-β-cyclodextrin (HP-β-CD) was incorporated into a poly(ether- block -amide) (Pebax) layer on a polysulfone support, followed by crosslinking with toluene 2, 4-diisocyanate to prepare a crosslinked HP-β-CD/Pebax (CHP) membrane. By adjusting the initial HP-β-CD concentration ( x ) and crosslinking reaction time ( y ), the microporous structure and surface morphology of CHP x – y ( x = 0, 0.25, 0.5, 0.75; y = 5, 10, 15) membranes could be manipulated. The OSN performances of the CHP x – y membranes were evaluated by the removal of dyes in methanol solution. The results revealed that the optimal CHP0.5–10 membrane exhibited a high methanol permeance of 8.7 L m −2 h −1 bar −1, high dye rejection (>96%), and high running stability (at least 336 h), due to the intrinsically microporous structure and surface morphology. This work would inspire the further development of cyclodextrins and other macrocyclic molecules in the preparation of OSN membranes and provide a promising strategy to fabricate state-of-the-art membranes for the efficient separation of organic solvent reclamation and removal of organic pollutants.